Avaliaç\~ao de Impacto do Programa de Agricultura de Baixo Carbono no Brasil - Felipe Pinto da Silva; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– Since the 1990s, Brazilian agriculture has taken a leading role in sustainable development. In this context, the United Nations Conference on the Environment (Rio-92) was held in Rio de Janeiro, the release of satellite images that reduced deforestation rates in the Amazon, and the implementation of the Forest Code and the creation of the ABC Program (Low Carbon Agriculture). The program aims to disseminate sustainable productive practices through specific lines of financial credit. The present study measures the impact (or causal effect) of the ABC Program on production per GHG emissions. In order to evaluate this effect, a synthetic control model was built to compare Brazil (treated group) with the rest of the world (control group), from 2000 to 2015. The results showed that the impact of the program is null on the interest variable in the post-intervention.
Keywords: Q10; Q14; Q20; 330; agriculture; sustainability; emissions; low carbon economy